Characterization of high-strength bolts and the numerical representation method for an efficient crash analysis. (July 2022) - Schauwecker, Florian; Moncayo, David; Middendorf, Peter
Graphical abstract: Highlights: Experiments show the necessity of the thread for numerical bolt representations. Calibration of bolt specific material cards with low experimental expenditure. Approach comprising solid elements with a material card including damage and failure. Numerical behavior of a fine-meshed bolt representation with regard to the thread. Prediction capability of a coarse-meshed model including tension-shear superposition. Abstract: This paper presents novel insights of a numerical bolt representation approach taking into account damage and failure, suitable for large-scale models as in full vehicle crash simulations. Custom-built experimental equipment combined with digital image correlation enables observation of bolt failure behavior and its physical characteristics under tension, shear as well as combined loading. A fine-meshed model demonstrates the transferability of the physical properties to numerics including the associated restrictions. The experimental and numerical findings are used to develop an efficient substitute bolt model with high prediction accuracy that takes into account the bolt kinematics due to the thread via volume elements. An isotropic constitutive law with linear elastic and multilinear plastic progression supplemented by a phenomenological damage model depicts the bolt material behavior numerically. The observation of the bolt models under different tension and shear ratios provides new insights to the models accuracy which is assessed by an analytically failure envelope.